Combating the exploitation of children in cyberspace: emerging research and opportunities - Elshenraki, Hossam Nabil (Advances in criminology, criminal justice, and penology (ACCJP), 2021)
""This book explores the elements of combating cyber exploitation against children. It also examines the education of parents, children, and other bodies on how to protect and create an awareness of threats and risks online"--Provided by publisher"--